Effect of individual parameter changes on the outcome of the estimated short-term dietary exposure to pesticides. Issue 6 (3rd June 2018) - van der Velde-Koerts, Trijntje; Breysse, Nicolas; Pattingre, Lauriane; Hamey, Paul Y.; Lutze, Jason; Mahieu, Karin; Margerison, Sam; Ossendorp, Bernadette C.; Reich, Hermine; Rietveld, Anton; Sarda, Xavier; Vial, Gaelle; et al.
ABSTRACT: In 2015 a scientific workshop was held in Geneva, where updating the International Estimate of Short-Term Intake (IESTI) equations was suggested. This paper studies the effects of the proposed changes in residue inputs, large portions, variability factors and unit weights on the overall short-term dietary exposure estimate. Depending on the IESTI case equation, a median increase in estimated overall exposure by a factor of 1.0-6.8 was observed when the current IESTI equations are replaced by the proposed IESTI equations. The highest increase in the estimated exposure arises from the replacement of the median residue (STMR) by the maximum residue limit (MRL) for bulked and blended commodities (case 3 equations). The change in large portion parameter does not have a significant impact on the estimated exposure. The use of large portions derived from the general population covering all age groups and bodyweights should be avoided when large portions are not expressed on an individual bodyweight basis. Replacement of the highest residue (HR) by the MRL and removal of the unit weight each increase the estimated exposure for small-, medium- and large-sized commodities (case 1, case 2a or case 2b equations). However, within the EU framework lowering of the variability factor from 7 or 5 to 3 counterbalances the effect of changes in other parameters, resulting in an estimated overall exposure change for the EU situation of a factor of 0.87-1.7 and 0.6-1.4 for IESTI case 2a and case 2b equations, respectively.